Hasil turunan dari fungsi
turunan dari bentuk
U/V = (U'V – UV') / V^2
1. U = 3x^2 – 2x
U' = 6x – 2
V = x^2
V' = 2x
U/V = (6x-2)(x^2) – (3x^2-2x)(2x) / (x^2)^2
= 6x^3 – 2x^2 – 6x^3 + 4x^2 / x^4
= 2x^2 / x^4
= 2 / x^2
2. U = x^2 – x
U' = 2x – 1
V = x+3
V' = 1
= (2x-1)(x+3) – (x^2-x)(1) / (x+3)^2
= 2x^2 + 5x – 3 – x^2 + x / (x+3)^2
= x^2 + 6x – 3 / (x+3)^2
3. U = x^3 – 2x
U' = 3x^2 – 2
V = x^2
V' = 2x
= (3x^2-2)(x^2) – (x^3-2x)(2x) / (x^2)^2
= 3x^4 – 2x^2 – 2x^4 + 4x^2 / x^4
= x^4 + 2x^2 / x^4
= x^2 + 2 / x^2